Synthesis and interaction studies of Naphthalimide-Azide based probes with Serum Albumins - Komal, Verma (My University, 2023)
Naphthalimide based chemosensors (Probe 1 and Probe 2) were developed for sensing Bovine Serum Albumin and Human Serum Albumin. Preliminary selectivity analysis confirmed that both the probes were highly selective towards BSA and HSA as compared to other bio analytes. Fluorescence spectroscopy analysis showed that addition of both probes 1 and 2 lead to hypochromic shift in the spectra of both BSA and HSA, at 330nm. The binding affinity of BSA-probe complex was found to be 1.7 x 105 M-1 and 3.1 x 105 M-1 for probes 1 and 2, respectively and for HSA-probe were 0.5 x 105 M-1 and 3.1 x 105 M-1 for probes 1 and 2, respectively. This indicated that probe 2 has better sensing ability towards both BSA and HSA. The probes and albumin proteins were found to bind in 1:1 stoichiometry, as the number of binding sites were 1.0 for both BSA-probe and HSA-probe complexes. Furthermore, the protein-ligand binding site studies indicated that both probes bind at Suldow’s site III, (binding site for Bilirubin) of the BSA. Cell viability assay confirmed the newly synthesised probe 2 is non-toxic towards Human Embryonic Kidney (Hek293) cell line, therefore, it can be explored for its biological applications.
Keywords: Naphthalimide; Azide; Tryptamine; Human Serum Albumin; Bovine Serum Albumin